Fantastic four

Algebra Level 3

f ( a + b ) = f ( a ) + f ( b ) + 4 a b \large f(a+b)=f(a)+f(b)+4ab

The functional equation above is true for all real numbers a a and b b . Find the value of f ( 4 ) f\left( 4 \right) , given that f ( 4 ) = 40 f\left( -4 \right) =40 .


The answer is 24.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

3 solutions

Rishabh Jain
Jun 24, 2016

Put a = b = 0 a=b=0 in the equation: f ( 0 ) = 2 f ( 0 ) + 0 f ( 0 ) = 0 f(0)=2f(0)+0\implies \color{#D61F06}{f(0)=0}

Put a = x , b = x a=x,b=-x in the equation:

f ( 0 ) 0 = f ( x ) + f ( x ) 4 x 2 \color{#D61F06}{\underbrace{f(0)}_0}=f(x)+f(-x)-4x^2 f ( x ) = 4 x 2 f ( x ) ( G e n e r a l i s a t i o n ) \implies f(x)=4x^2-f(-x)~~(\small{\color{grey}{Generalisation}})

Put x = 4 x=4 so that:

f ( 4 ) = 4 ( 4 ) 2 40 = 24 f(4)=4(4)^2-40=\large{\boxed{24}}

That's a different approach, + Γ ( 2 ) + \Gamma(2)

Mehul Arora - 4 years, 11 months ago

Log in to reply

Thanks.... :-)

Rishabh Jain - 4 years, 11 months ago

Does such a functional equation exist? Otherwise, the answer might have been "undefined".

Calvin Lin Staff - 4 years, 11 months ago

Log in to reply

f ( x ) = 2 x 2 f(x)=2x^2 is satisfying the given condition but f ( 4 ) 40 f(-4) \ne 40

Sabhrant Sachan - 4 years, 10 months ago

Awesome solution..your maths is cool.

Rishu Jaar - 3 years, 7 months ago

f ( a + b ) = f ( a ) + f ( b ) + 4 a b f ( a ) = f ( a ) + f ( 0 ) f ( 0 ) = 0 f ( 4 + 4 ) = 0 f ( 4 ) + f ( 4 ) 64 = 0 40 64 + f ( 4 ) = 0 f ( 4 ) = 24 f(a+b)=f(a)+f(b)+4ab\\\Rightarrow f(a)=f(a)+f(0)\\\Rightarrow f(0)=0\\\Rightarrow f(-4+4)=0\\\Rightarrow f(-4)+f(4)-64=0\Rightarrow40-64+f(4)=0\Rightarrow f(4)=24

Chew-Seong Cheong
Jun 23, 2016

f ( 4 ) = 40 f ( 2 2 ) = 40 f ( 2 ) + f ( 2 ) + 4 ( 2 ) ( 2 ) = 40 2 f ( 2 ) + 16 = 40 2 f ( 2 ) = 24 f ( 2 ) = 12 \begin{aligned} f(-4) & = 40 \\ f(-2-2) & = 40 \\ f(-2)+f(-2)+4(-2)(-2) & = 40 \\ 2f(-2) + 16 & = 40 \\ 2f(-2) & = 24 \\ \implies f(-2) & = 12 \end{aligned}

f ( 4 2 ) = f ( 4 ) + f ( 2 ) + 4 ( 4 ) ( 2 ) f ( 2 ) = f ( 4 ) + 12 32 f ( 4 ) = f ( 2 ) + 20 . . . ( 1 ) \begin{aligned} f(4-2) & = f(4) + f(-2) + 4(4)(-2) \\ f(2) & = f(4) + 12 - 32 \\ \implies f(4) & = f(2) + 20 \quad ...(1) \end{aligned}

f ( 2 + 2 ) = f ( 2 ) + f ( 2 ) + 4 ( 2 ) ( 2 ) f ( 4 ) = 2 f ( 2 ) + 16 . . . ( 2 ) \begin{aligned} f(2+2) & = f(2) + f(2) + 4(2)(2) \\ \implies f(4) & =2 f(2) + 16 \quad ...(2) \end{aligned}

2 × ( 1 ) ( 2 ) : f ( 4 ) = 40 16 = 24 \begin{aligned} 2 \times (1)-(2): \quad f(4) & = 40 - 16 = \boxed{24} \end{aligned}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...